FINDINGS OF THE HUMAN SKELETON IN SEMEDO SITE - Alifah Alifah (Pusbindiklat - LIPI, 2012)
Semedo is a site with archaeological potential of animal vertebrate fossils and stone tools. Human fossilsas cultural actors on the site until now has not been found. In early January 2011, people found the order ofhuman skeleton on this site. This research was conducted with the objective of identifying the human species andits relationship with the fossil vertebrates and stone tools available at this site. The method used in this study is asurvey of observations and literature studies. This research is important given the results of this study will be usedas a basis for policy making and management framework of the findings Semedo Site.